Discovery of imidazole-based GSK-3β inhibitors for transdifferentiation of human mesenchymal stem cells to neurons: A potential single-molecule neurotherapeutic foresight - Gupta, Varsha; Mahata, Tanushree; Roy, Rajsekhar; Gharai, Prabir Kumar; Jana, Aniket; Garg, Shubham; Ghosh, Surajit (Frontiers in Molecular Neuroscience, 2022)
The transdifferentiation of human mesenchymal stem cells (hMSC) to functional neurons is crucial for the development of future neuro-regenerative therapeutics. Currently, transdifferentiation of hMSCs to neurons requires a “chemical cocktail” along with neural growth factors. The role of the individual molecules present in a “chemical cocktail” is poorly understood and may cause unwanted toxicity or adverse effects. Toward, this goal, we have showcased the discovery of an imidazole-based “single-molecule” transdifferentiation initiator SG-145C. This discovery was achieved via screening of a small molecule library through extensive in silico studies to shortlist the best-fitting molecules. This discovery evolved through a careful selection to target Glycogen synthase kinase-3β (GSK-3β), which is one of the important proteins responsible for neurogenesis. Rigorous computational experiments, as well as extensive biological assays, confirmed that SG-145C has significant potential to transdifferentiate hMSCs to neurons. Interestingly, our results suggest that SG-145C can inhibit the proteasomal degradation of phosphorylated β-catenin, in turn promoting transdifferentiation of hMSCs into neurons via the Wnt pathway.